Professionalism in Radiology: A Guide for Residents and Medical Students - Andrea Donovan; Petra Lewis; Sravanthi Reddy; Christopher Straus (Association of American Medical Colleges, 2012)
Abstract Professionalism is fundamental to the practice of radiology. Several studies have documented that improvement is needed in areas such as patient safety, ethical conduct, and communication of information. The Accreditation Council for Graduate Medical Education recently called for changes in medical education to improve the quality of health care delivery. In addition to medical knowledge, this governing body now requires that professionalism be taught and evaluated during residency training. There is a paucity of resources that facilitate self-directed and small-group learning using case-based teaching to promote professionalism among medical students and residents in radiology. Thus, this resource was created to fill that gap. It consists of two PowerPoint learning modules (one for residents and one for medical student learners), as well as pre- and posttest questions. The module should be viewed as a slide show to activate all of the interactive components in the questions and answers. The main purpose of this learning resource is to provide a self-directed module to help the learner understand some of the issues around professionalism in radiology and to apply this knowledge to specific scenarios. A second goal is to provide a venue in which to evaluate this knowledge using a pre- and posttest associated with the module.